Crime de frustração do caráter competitivo de licitação (ART. 337-F do CP) : bem jurídico, tipicidade e ofensividade - Vieira, Jorge Cley Maritns (2022)
It is proposed in the present dissertation, linked to the line of research of Penal system and violence, of the PPGCrim of PUCRS, to research the changes in the criminal sphere imposed from the legislative alteration of the Law of Public Procurement and Administrative Contracts (Law nº 14,133, of 1st of April 2021), which revoked arts. 89 to 108 of Law nº 8.666/93, at the time that it implemented Chapter II-B in the Penal Code (On crimes in public tenders and administrative contracts, with insertion in Title XI of the Special Part – On crimes against the Public Administration. explore the crime of frustration of the competitive nature of bidding (art. 337-F of the CP), from which a detailed analysis was made from the perspective of the theory of the legal interest, including from the perspective of supra-individual legal interests, associated with the dictates constitutional provisions that limit the state's punitive action, with emphasis on the offensiveness of the conduct. In addition, the bidding institute is generally approached, observing its general and special principles, hypotheses of protected goods and the implicit constitutional commandment of criminalization. It also focuses on the analytical study of the crime of frustration of the competitive nature of bidding (art. 337-F of the CP), whose particularities allow verifying the objective and subjective elements of the type, reaching a crime classified as a cut result, whose criminal legislative technique is only sustained in the face of a robust and justified hypothesis of offense.